2018
DOI: 10.1101/346601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glucose signaling is important for nutrient adaptation during differentiation of pleomorphic African trypanosomes

Abstract: 18The African trypanosome has evolved mechanisms to adapt to changes in 19 nutrient availability that occur during its lifecycle. During transition from mammalian 20 blood to insect vector gut, parasites experience a rapid reduction in environmental 21 glucose. Here we describe how pleomorphic parasites respond to glucose depletion 22 with a focus on parasite changes in energy metabolism and growth. Long slender 23 bloodstream form parasites are rapidly killed as glucose concentrations fall, while the 24 short… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…This suggests that AAT7-B expression is connected to a switch in energy metabolism. While AAT7-B genes are expressed in all developmental stages, transcript levels of the individual genes were found to differ between BSF and PCF in several studies; these consistently showed a prevalence of Tb927.8.7610 in BSF and Tb927.8.7640 in the procyclic form ( 17 , 39 , 41 , 42 , 43 , 44 , 45 , 46 , 68 ). This is comparable to our results with approx.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that AAT7-B expression is connected to a switch in energy metabolism. While AAT7-B genes are expressed in all developmental stages, transcript levels of the individual genes were found to differ between BSF and PCF in several studies; these consistently showed a prevalence of Tb927.8.7610 in BSF and Tb927.8.7640 in the procyclic form ( 17 , 39 , 41 , 42 , 43 , 44 , 45 , 46 , 68 ). This is comparable to our results with approx.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that short stumpy BSF preadapts to life in their future insect host ( 69 ), for example, by increasing expression of enzymes of the TCA cycle, change of their excreted end products from pyruvate toward acetate and succinate ( 39 , 69 , 70 , 71 ), and by elevating transcripts of proline-metabolizing enzymes ( 17 , 39 , 41 ). Though higher AAT7-B transcript or protein levels were occasionally identified in short stumpy BSF ( 17 , 72 ), in the majority of studies no major regulation was reported ( 41 , 45 , 46 , 68 ) indicating that AAT7-B expression may be altered only once stumpy forms enter the insect host i.e. , during the transition to procyclic forms and induced by nutrient or energy availability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility is a response to stress, although there was no correlation with the effects of heat shock (Minia, Merce, Terrao, & Clayton, ) or starvation (Fritz et al, ). Altered metabolite levels could also be responsible (Bringaud et al, ; Fernandez‐Moya, Carrington, & Estevez, ; Qiu et al, ; Vassella et al, , ); and it is conceivable that one or more of the directly regulated surface proteins acts as a receptor for a signal that maintains procyclic identity.…”
Section: Discussionmentioning
confidence: 99%